Impaired theory of mind and emotion recognition in pediatric bipolar disorder: A systematic review and meta-analysis. (June 2021) - Halac, Eren; Ciray, Remzi Ogulcan; Turan, Serkan; Tuncturk, Mustafa; Agac, Nilay; Elmas, Fatma Nur; Rosson, Stella; Ermis, Cagatay
Abstract: Background: Social cognition is impaired in patients with severe mental disorders. We aimed to investigate impairments in social cognition in youth with pediatric bipolar disorder (PBD) through a systematic review of the literature and the meta-analysis. Method: Following the PRISMA guidelines, we searched in PubMed, Scopus, and Cochrane CENTRAL for studies reporting on the theory of mind (ToM) and emotion recognition (ER) abilities of patients with PBD compared to healthy controls (HC). We conducted a random-effects model meta-analysis for the contrast between PBD and HC. Subgroup and meta-regression analyses were conducted for demographic and clinical variables as appropriate. Results: A total of thirteen studies involving 429 patients with PBD and 394 HC were included. Patients with PBD had significantly poorer social cognitive abilities (Hedges' g for ER, g = −0.74, CI = −0.91, −0.57; and for ToM, g = −0.98, CI = −1.41 to −0.55). Subgroup analysis also revealed significant impairment in ER for patients in a euthymic state (g = −0.75). Age, gender, sample size, the severity of mood symptoms, estimated IQ, the frequencies of bipolar-I disorder, attention-deficit hyperactivity disorder, medications, study quality and euthymia did not moderate the difference in meta-regression. Heterogeneity was low in all analyses and there was no evidence for publication bias. Conclusion: The results of this meta-analysis supported the notion that PBD is associated with a deficit in social cognitive abilities at a medium to a large level. Impairments in social cognition could be an illness-related trait of PBD. Meta-regression results did not find a moderator of the deficits in social cognition. Highlights: Theory of Mind (ToM) and Emotion Recognition (ER) were impaired in pediatric bipolar disorder (PBD). Social cognitive impairments in PBD yielded moderate to large effect sizes. The impairments in social cognition (SC) were independent of the presence of manic symptoms. Meta-regression did not yield a significant moderator of the deficits in SC.